Aplikasi Media Pembelajarangames Edukasi Berbasis Android (Kasus Kelas 1 SDN 546 Sinangkala) - Iis Hidayah; Budiawan Sulaeman; Hisma Abduh (LPPM STIKOM Tunas Bangsa, 2022)
This study aims to design and build an Android-based educational media application for educational games. The research method used is a qualitative method using data collection techniques from observations, interviews, and literature searches. Learning media application It was developed using the waterfall system development methodology. The software used to design and implement the system uses Adobe Flash Professional CS6 as the system design. Educational Game Learning Media Applications It contains quiz and game material. The application that has been built has been tested on users so that it is obtained an application that runs well